Rapid MALDI-MS/MS-Based Profiling of Lipid A Species from Gram-Negative Bacteria Utilizing Trapped Ion Mobility Spectrometry and mzmine - Rudt, Edward; Froning, Matti; Heuckeroth, Steffen; Ortmann, Lucas; Diemand, Julia; Hörnschemeyer, Linus; Pleger, Alexander; Vinzelberg, Max; Schmid, Robin; Pluskal, Tomáš; Dobrindt, Ulrich; Hayen, Heiko; et al. (Analytical chemistry, 2025)
Lipid A, a crucial component of lipopolysaccharides (LPS), plays a pivotal role in the pathogenesis of Gram-negative bacteria. Lipid A patterns are recognized by mammals and can induce immunostimulatory effects. However, the outcome of the interaction is highly dependent on the chemical composition of individual lipid A species. The diversity of potential fatty acyl and polar headgroup combinations in this complex saccharolipid presents a significant analytical challenge. Current mass spectrometry (MS)-based lipid A methods are focused on either direct matrix-assisted laser desorption/ionization (MALDI)-MS screening or comprehensive structural elucidation by tandem mass spectrometry (MS/MS) hyphenated with separation techniques. In this study, we developed an alternative workflow for rapid lipid A profiling covering the entire analysis pipeline from sample preparation to data analysis. This workflow is based on microextraction and subsequent MALDI-MS/MS analysis of uropathogenic Escherichia coli utilizing trapped ion mobility spectrometry (TIMS), followed by mzmine data processing. The additional TIMS dimension served for enhanced sensitivity, selectivity, and structural elucidation through mobility-resolved fragmentation via parallel accumulation-serial fragmentation (PASEF) in parallel reaction monitoring (prm)-mode. Furthermore, mzmine enabled automated MS/MS acquisition by adapting the spatial ion mobility-scheduled exhaustive fragmentation (SIMSEF) strategy for MALDI spot analysis. It also facilitated robust lipid A annotation through a newly developed extension of the rule-based lipid annotation module, allowing for the custom generation of lipid classes, including specific fragmentation rules. In this study, the first publication of lipid A species' collision cross section (CCS) values is reported, which will enhance high-confidence lipid A annotation in future studies.
Keywords: tandemová hmotnostní spektrometrie; uropatogenní Escherichia coli; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Uropathogenic Escherichia coli; Ion Mobility Spectrometry; gramnegativní bakterie; Gram-Negative Bacteria; Lipid A; Tandem Mass Spectrometry; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; lipid A; iontová mobilní spektrometrie